CORRELATION OF TMPRSS2-ERG GENE FUSION STATUS WITH CLINICOPATHOLOGICAL CHARACTERISTICS IN PROSTATE CANCER OF IRAQI PATIENTS - A., Ammar K.; Altaee, M. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of this study was to establish the existence and interaction of TMPRSS2 – ERG gene fusion status with clinicopathological features of prostate cancer patients. This research consisted of 123 embedded formalin-fixed tissues obtained from the prostate tumor patients. The above gene fusion is detected through the technique of fluorescent in situ hybridization (FISH) by means of a triple color probe. Seven samples have not been scored due to technical difficulties and 46 patients have fusion (39.6%), while the remaining (70) have not been seen with fusion. Of the 46 fusion-positive, 17 (36%) were caused by ERG-translocation, of the other 29 (63%) were caused by the interstitial segment deletion between the two genes due to their sequential position. In order to find a substantial correlation between 116 patients (fusion took place in 46 and non-fusion in 70) with clinicopathological features, the following findings were calculated: Our findings recorded non-significant correlation at age, BMI and tumor size at which (P-value >0.05).While results showed significant association with: pathological T stage (P value = 0.011), Gleason score (P value = 0.002), perineural invasion (P value = 0.047) and PSA (P value = 0.033). The clinicopathological features which had a considerable correlation with fusion status are very important as they aid the doctors in prognosis and treatment of such tumor.